Pelatihan Pengisian Instrumen Akreditasi Berbasis Online Evaluasi Diri Madrasah - Khairul Anwar; Abdul Majir; Masriani Masriani; Ismail Nasar; Nova Asvio (Institut Agama Islam Negeri Bengkulu, 2022)
This community service is carried out with the main focus on the ability of teachers and madrasah principals to fill out the accreditation instrument developed by the online-based School Accreditation Board. The objectives of this community service are: to increase the understanding of teachers and madrasah principals about the concept of self-evaluation in the context of internal quality assurance for schools/madrasas, improve the skills of teachers and principals in filling out accreditation instruments based on the implementation of school/madrasah self-evaluations, and increase awareness teachers and madrasah principals about the importance of internal school/madrasah quality assurance.The method used to achieve this community service goal uses: socialization and focus group discussions on madrasa self-evaluation materials as part of the implementation of internal school quality assurance, assistance in filling out accreditation instruments developed by BAN S/M, discussion and reflection. The outputs that have been produced through this activity are: 1) the implementation of socialization activities and discussions focused on the material for accreditation instruments at the Madrasah Ibtida'iyah level 2) the implementation of assistance activities for filling out accreditation instruments, and 3) the compilation of articles published in community service journals. Thus, it is hoped that there will be positive implications for other schools in preparation for school accreditation so that the results achieved are maximized.